Brand Strategy, Product Quality, and Customer Experience as Determinants of Loyalty - Sinatria Rizki Pratama; Kartika Hendra Ts; Anita Wijayanti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to determine the effect of simultaneously (simultaneously) or partially the variables of brand identity, brand communication, product quality and customer experience at Hotway's Chicken Solo. This research method uses a quantitative research design. The population in this study was 90 loyal customers of Hotway's Chicken Solo. The sampling technique used in this study is the survey approach technique with a sample of 90 respondents. Collecting data by using a questionnaire. The data analysis technique used was statistical analysis, namely multiple linear regression test, F test, t test, and the coefficient of determination. The results showed that brand identity, brand communication, product quality and customer experience simultaneously and significantly affected the customer loyalty at Hotway's Chicken Solo. Suggestions from this study are, for Hotway's Chicken Solo continues to improve Brand Identity, Brand Communication, Product Quality and Customer Experience so that it will make Customer Loyalty increase and be better than before.